Coordination failures in immigration policy - Paolo E. Giordani; Michele Rutaz (World Trade Organization (WTO), 2011)
We propose a theoretical framework for analyzing the problems associated to unilateral immigration policy in receiving countries and for evaluating the grounds for reform of international institutions governing immigration. We build a model with multiple destination countries and show that immigration policy in one country is influenced by measures adopted abroad as migrants choose where to locate (in part) in response to differences in immigration policy. This interdependence gives rise to a leakage effect of immigration policy, an international externality well documented in the empirical literature. In this environment, immigration policy becomes strategic and unilateral behavior may lead to coordination failures, where receiving countries are stuck in welfare inferior equilibria. We then study the conditions under which a coordination failure is more likely to emerge and argue that multilateral institutions that help receiving countries make immigration policy commitments would address this ineffuciency.
Keywords: F02; F22; J61; 330; immigration policy; cross-border externalities; coordination failures; multilateral institutions